Association of ambient ozone with pneumonia hospital admissions in Hong Kong and Taipei: A tale of two Southeast Asian cities. (November 2021) - Qiu, Hong; Chuang, Kai-Jen; Bai, Chyi-Huey; Fan, Yen-Chun; Chang, Ta-Pang; Yim, Steve Hung-Lam; Wong, Tze-Wai; Ho, Kin-Fai
Highlights: Age-specific pneumonia risk of O3 was evaluated in two Southeast Asian cities. Harvesting effects of O3 on pneumonia hospitalizations could not be excluded in children. Short-term O3 exposure was associated with pneumonia hospitalizations in the elders. The associations were robust with different O3 metrics in Hong Kong and Taipei. Abstract: Ozone (O3 ) is a reactive oxidant exerting both inflammatory and oxidative damages to the respiratory system. With the ground-level O3 progressively increasing in the past decade, the reevaluation of the pneumonia hospitalization risk from exposure to O3 is of public health interest. We conducted an ecological time-series study to examine the city-specific association between short-term O3 exposure and pneumonia hospitalizations in Hong Kong and Taipei, respectively. We linked the daily pneumonia hospitalization count to air pollution concentrations and weather conditions according to the date of admission during 2010–2017. We applied a generalized additive distributed lag model to examine the association while adjusting for time-varying covariates. Stratified analysis by age group and the potential harvesting effect of O3 were evaluated. We observed the harvesting effects of O3 on pneumonia hospitalizations in children in both cities and adults in Taipei. The short-term effect of O3 lasted for around one week. An interquartile range (IQR) increment of daytime 8-hour mean concentration of O3 distributed over 0–6 lag days in Hong Kong (42.4 μg/m 3 ) was associated with a 7.04% (95% CI: 5.35–8.76%) increase in hospital admissions for elderly pneumonia, while the corresponding cumulative excess risk per IQR increment of O3 in Taipei (38.7 μg/m 3 ) was 3.41% (95% CI: 1.63–5.22%). Different O3 metrics, varying degrees of freedom for filtering the temporal trend, and three-pollutant models supported the robustness of the associations. We concluded that short-term O3 exposure was associated with pneumonia hospitalizations in the elderly population. Understanding the pneumonia hospitalization risk of O3 will help to inform public health policies in the planning of ozone control strategies and intervention measures to prevent ozone-related pneumonia in vulnerable elderly populations.